Pengaruh Profitabilitas, Likuiditas Dan Kebijakan Utang Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur - Winna, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2019)
Companies that have policies in paying dividends every year are still relatively small. The purpose of this study is to determine the effect of profitability, liquidity and debt policy on dividend policy. This study took manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017 as subject of research with purposive sampling technique in determining the research sample. Data analysis was performed by multiple linear regression with the help of SPSS version 23. The results showed that: (1) Profitability partially had a positive and significant effect on dividend policy, (2) Liquidity partially had a positive but not significant effect on dividend policy, (3 ) The debt policy partially has a positive and significant effect on dividend policy, and (4) Profitability, liquidity and debt policy simultaneously have a significant effect on dividend policy.